(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
On the perspective of teacher job burnout, this study takes the intervention pathway for primary school music teacher burnout as the research object. Based on the excavation, collection, organization, reading, and analysis of literature, combined with relevant theories of psychology and education, using methods such as literature review, questionnaire survey, analysis, and data statistics, the paper studies the impact and effectiveness of workload on the job burnout of primary school music teachers.